Raman Spectroscopy of CaCu3Ti4O12 Ceramics Revisited - Nhat, Hoang Nam (VNU Journal of Science: Mathematics - Physics; Vol 34 No 3, 2018)
The CaCu 3 Ti 4 O 12 ceramic has been prepared by Solid State Reaction method in excess oxygen. It possesses a well-defined double-perovskite type crystalline structure and exhibits a colossal dielectric constant at around 50000 at room temperature. This paper revised the imprints of Raman spectroscopy of this compound to validate its structural characteristics and optical behaviors. A special attention is paid on the account of optical phonons which show a recognizable agreement with the other results recently reported